2022
DOI: 10.1186/s13690-022-00942-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of anemia among adolescent girls in Ethiopia: a systematic review and meta-analysis

Abstract: Background In Ethiopia, there are primary studies on adolescent anemia with imprecise and inconclusive findings. Besides, there was no meta-analysis pooled the magnitude and associated factors of anemia among adolescent girls in Ethiopia. Estimating the pooled magnitude and associated factors of anemia among adolescent girls is helpful for evidence-based interventions in Ethiopia. Methods The authors used a preferred reporting item for systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Girls living in rural areas face a higher risk of developing anemia compared to their counterparts in urban areas. This finding aligns with a systematic review and meta-analysis conducted in Ethiopia 76 . This finding is also supported by another study conducted in Ethiopia 16 .…”
Section: Discussionsupporting
confidence: 91%
“…Girls living in rural areas face a higher risk of developing anemia compared to their counterparts in urban areas. This finding aligns with a systematic review and meta-analysis conducted in Ethiopia 76 . This finding is also supported by another study conducted in Ethiopia 16 .…”
Section: Discussionsupporting
confidence: 91%
“…It is against this background that efforts to address anaemia among adolescents should be considered on public health agenda in Gulu district and city in particular and Acholi sub-region in general although the prevalence still falls under mild category according to public health signi cance [33]. This is because mild anaemia was reported to have health consequences on the adolescent girls such as reproductive age; risk of low birth, preterm delivery, perinatal mortality, and postpartum haemorrhage [44]. Furthermore, although the results of the current study cannot be generalised to other parts of Uganda and the rest of the world, the ndings of the current study still provide an important information that can give insight into a large-scale study and provoke mechanisms for addressing iron de ciency anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors [44] reported that differences in magnitude of anaemia could be due to differences in economy, socio-culture, and dietary practices. In our study, socio-economic and demographic factors of the adolescents like age of respondent, caretaker of the respondent, class of the respondent, highest level of education of the parent/guardian, household size, occupation of the parent/guardian, nature of the menstrual ow, and duration of menstruation (days) were considered and tested whether they had association with dietary quality and micronutrient adequacy.…”
Section: Socio-economic and Demographic Factors Associated With Dieta...mentioning
confidence: 99%
“…Menurut hasil penelitian Kidanemaryam, dkk. 2022, menyatakan bahwa ada hubungan yang signifikan antara IMT kurus dengan kejadian anemia pada remaja putri hasil uji statistik didapatkan nilai sig-p = 0,000 < 0,05 (8).…”
Section: Faktor-faktor Yang Menyebabkan Terjadinya Anemia Pada Remaja...unclassified